Respuesta :
g(x) will be g(x)=-2x-3 because it is a reflection of f(x) over the x-axis. F(x)'s reflection over the x-axis will become -f(x).
Answer:
[tex]g(x)=-x^2-3[/tex]
Step-by-step explanation:
The parent function is [tex]x^2+3[/tex]
Now, the function g(x) is obtained by reflecting the graph of f(x) about the x-axis.
When the parent function f(x) is reflected about the x-axis then the translated function is -f(x)
Therefore, we have g(x)=-f(x)
Hence, the equation of g(x) is
[tex]g(x)=-f(x)\\\\g(x)=-(x^2+3)\\\\g(x)=-x^2-3[/tex]